2009
DOI: 10.1111/j.1526-4637.2009.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of Pulsed Radiofrequency Treatment of Myofascial Trigger Points and Scar Neuromas: Table 1

Abstract: Our review suggests that PRF could be a minimally invasive, less neurodestructive treatment modality for these painful conditions and that further systematic evaluation of this treatment approach is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 16 publications
(20 reference statements)
0
23
0
Order By: Relevance
“…For other locations, where concerns about loss of sensory and motor function exist, pulsed radiofrequency ablation provides an opportunity for nerve regrowth. [95][96][97] Current literature suggests that pulsed radiofrequency ablation delivers an electromagnetic field, which modifies neurocellular function with minimal cellular destruction. 98 Radiofrequency ablations may be performed real time under ultrasound guidance after identification of the neuroma and diagnostic local anesthetic injections (Fig.…”
Section: Pharmacological Managementmentioning
confidence: 99%
“…For other locations, where concerns about loss of sensory and motor function exist, pulsed radiofrequency ablation provides an opportunity for nerve regrowth. [95][96][97] Current literature suggests that pulsed radiofrequency ablation delivers an electromagnetic field, which modifies neurocellular function with minimal cellular destruction. 98 Radiofrequency ablations may be performed real time under ultrasound guidance after identification of the neuroma and diagnostic local anesthetic injections (Fig.…”
Section: Pharmacological Managementmentioning
confidence: 99%
“…12 PRF, which can be applied in a similar manner to CRFT applications (such as facet medial nerve or trigeminal nerve applications), is distinguished mainly by peripheral applications where CRFT is never applied. PRF has been reported to be used successfully in treatment of disorders such as myofascial trigger points, 11 phantom limb pain, 13 occipital neuralgia, 14 meralgia paresthetica, 15 and premature ejaculation. 16 One of the fields where PRF was claimed to be effective is that of intra-articular applications.…”
Section: Introductionmentioning
confidence: 99%
“…In PRF, the RF energy is applied at high voltage (typically 45 V) and with 20 millisecond bursts followed by 480 millisecond silent phases. 11 Thus, because of the long silent phase, the tissue temperature will be spread and will not exceed 42 C. So, no tissue damage will develop because the tissue temperature will remain below 45e50 C, which is considered as the irreversible tissue damage threshold. 12 PRF, which can be applied in a similar manner to CRFT applications (such as facet medial nerve or trigeminal nerve applications), is distinguished mainly by peripheral applications where CRFT is never applied.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism responsible for the action of PRF remains unclear, although there is some evidence for a neuromodulatory effect [11]. PRF has been used to treat trigger points [1213]. However, to the best of our knowledge, only one previous study has demonstrated the effect of PRF on the gastrocnemius for managing plantar heel pain [14].…”
Section: Introductionmentioning
confidence: 99%